2006
DOI: 10.1128/jvi.80.6.3000-3008.2006
|View full text |Cite
|
Sign up to set email alerts
|

Biological Relevance of a Stable Biochemical Interaction between the Tombusvirus-Encoded P19 and Short Interfering RNAs

Abstract: The Tomato bushy stunt virus (TBSV)-encoded p19 protein (P19) is widely used as a robust tool to suppress RNA interference (RNAi) in various model organisms. P19 dimers appropriate 21-nucleotide (nt) duplex short interfering RNAs (siRNAs) generated by Dicer presumably to prevent programming of the RNA-induced silencing complex (RISC). In the context of virus infection, this model predicts that P19 mutants compromised for siRNA binding cannot prevent RISC-mediated degradation of TBSV RNA and thus reduce viral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
79
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 44 publications
8
79
1
2
Order By: Relevance
“…1C). Previously, it was shown that, in plants infected with wt Tombusvirus, viral-derived siRNAs exclusively associated with P19 (12,14,29). These findings, along with those reported here, agree with the model that, during infection, wtP19 dimers sequester Dicer-generated Ϸ21-nt TBSV duplex siRNAs to avoid their programming of a high-MW antiviral RISC-like complex and thus prevent the onset of RNAi-mediated viral RNA degradation (2).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…1C). Previously, it was shown that, in plants infected with wt Tombusvirus, viral-derived siRNAs exclusively associated with P19 (12,14,29). These findings, along with those reported here, agree with the model that, during infection, wtP19 dimers sequester Dicer-generated Ϸ21-nt TBSV duplex siRNAs to avoid their programming of a high-MW antiviral RISC-like complex and thus prevent the onset of RNAi-mediated viral RNA degradation (2).…”
supporting
confidence: 81%
“…The progression of infection and symptom development on N. benthamiana plants inoculated with a TBSV p19-mutant devoid of P19 expression (TBSV-dP19) is initially very similar to that observed for wt TBSV (9,14,15). However, instead of eventually succumbing to a lethal necrosis, plants infected with tombusviruses devoid of P19 expression develop a recovery phenotype associated with viral RNA clearance (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated that the tomato miRNA pathway is markedly compromised by P19, in particular when this protein is relatively abundant, as occurs during natural infection [52]. P19 is a high-affinity short (19-21 nt) double-stranded RNAbinding protein and that dimers of P19 bind siRNA duplexes in a 1 : 1 stoichiometric ratio [53][54][55][56]. This binding prohibits bound duplexes from unwinding and programming the RISC [57].…”
Section: Viral Stress-related Mirnasmentioning
confidence: 91%
“…This binding prohibits bound duplexes from unwinding and programming the RISC [57]. As a consequence, RISC-mediated degradation of cognate viral RNAs is repressed [53].…”
Section: Viral Stress-related Mirnasmentioning
confidence: 99%